Drawing activities enhance preschoolers socio emotional development - Zakaria, Mohd Zafaren; Yunus, Faridah; Mohamed, Suziyani (Southeast Asia Early Childhood Journal, 2021)
Visual art activities such as the processing of output in the form of drawing encourage children to use their imagination, expression, and multiple intelligences. Through visual art activities, children can participate actively in a more enjoyable learning environment. Drawing is an essential part of children in the production of various forms that can cause excitement, enjoyment, and aesthetic pleasure, thus causing it to become an essential part of the socio emotional development component preschool curricula. The methodology used in this study was a qualitative case study method. The instrument used was a face-to-face semi-structured interview with four preschool teachers under the Ministry of Education, using a purposive sampling technique. The results explain that two themes can be drawn from the interview data, namely, (i) meaningful expression and (ii) active communication. Socio emotional development and imagination are closely related to each other and the main aspects of the development of children to self-control, empathise, and collaborate with others. Therefore, children with problems in the socio emotional development can use a drawing medium to create an imaginary context that might allow them to reassess their identity and do not make mistakes in school.